Thymic enlargement in childhood - Öcal, Turgay; Türken, Aydın; Çiftçi, Arbay Özden; Şenocak, Mehmen Emin; Tanyel, F. Cahit; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 2000)
Thymic masses constitute one of the least common mediastinal masses in childhood. While producing symptoms of airway compromise, they also raise the suspicion of malignancy when detected. Radiological, operative and pathological findings of patients that have been operated for thymic masses in our institution is presented in this paper. Nine patients were operated in our institution during a 12-year-period between 1985-1997 for thymic masses. Ages of the patients ranged from four months to 13 years. With the exception of one, who was diagnosed with a routine chest x-ray, all the patients had respiratory complaints. All the patients had been evaluated with computed tomography preoperatively. In total, seven sternotomies and four thoracotomies were performed to reach the anterior mediastinum. The distribution of masses was as follows two malignant thymomas, three thymic hyperplasia, one lymphocyte-rich thymoma, one epithelial thymoma, one cystic thymoma and one lymphoblastic lymphoma. Although rare, thymic enlargement may be a cause of intractable respiratory complaints in childhood. Because of the high incidence of primary malignancy of the mediastinal neoplasms in childhood, thymic enlargement requires accurate pathological diagnosis and treatment. Median sternotomy with intensive anesthetical care allows proper tumoral exposure.
Keywords: thymus; anterior-superior mediastinal mass; respiratory distress